2019
DOI: 10.1002/hep.30612
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Homeostasis in a Cholesterol 7α‐Hydroxylase and Sterol 27‐Hydroxylase Double Knockout Mouse Model

Abstract: Bile acids (BAs) are diverse molecules that are synthesized from cholesterol in the liver. The synthesis of BAs has traditionally been shown to occur through two pathways. Cholesterol 7α‐hydroxylase (CYP7A1) performs the initial and rate‐limiting step in the classical pathway, and sterol 27‐hydroxylase (CYP27A1) initiates the hydroxylation of cholesterol in the alternative pathway. While the role of individual BA species as physiological detergents is relatively ubiquitous, their endocrine functions as signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 32 publications
(31 reference statements)
2
32
0
Order By: Relevance
“…4 C). Of note, the most regulated protein among the differentially expressed proteins was CYP7A1 (Cholesterol 7 alpha-hydroxylase), a key regulator of hepatic cholesterol and bile acid metabolism 15 , 16 . CYP7A1 protein expression levels were significantly increased in INT-offspring (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 C). Of note, the most regulated protein among the differentially expressed proteins was CYP7A1 (Cholesterol 7 alpha-hydroxylase), a key regulator of hepatic cholesterol and bile acid metabolism 15 , 16 . CYP7A1 protein expression levels were significantly increased in INT-offspring (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CYP7A1 and CYP27A1, a cholesterol 7α-hydroxylase responsible for the classic pathway and a steroid 27-hydroxylase responsible for the alternative pathway for BA synthesis, were both suppressed in the KO MCD liver compared with the WT MCD liver. The BA level was reduced by 66.7% and 73% in Cyp7a1 −/− and Cyp27a1 −/− mice and even more in double-knockout ( Cyp7a1 −/− ; Cyp27a1 −/− ) mice ( Rizzolo et al., 2019 ), indicative of the critical roles of these two hydroxylases in the BA metabolism. In addition, levels of FXR, a negative regulator of BA production and a BA receptor, were significantly increased in KO MCD rats compared with WT MCD.…”
Section: Discussionmentioning
confidence: 99%
“…FXR was first widely recognized for regulating the bile acid pathway in the liver and intestines. Previous studies have demonstrated that FXR regulates the bile acid synthesis through two main pathways [ 32 34 ]. In the classical pathway, CYP7A1 is a liver-specific microsomal cytochrome P450 enzyme, which is a rate-limiting enzyme in the classic pathway of bile acid synthesis.…”
Section: Biological Characteristics Of Fxrmentioning
confidence: 99%